‘Alexa, I want the truth’: An Exploratory Investigation into the Privacy Concerns of Virtual Assistant AI Technology - Akhtar, Fareeha (2020)
Over the last few years virtual assistant AI technology has famously become an integral accessory within smart spaces. While the use of these devices increases accessibility and facilitates convenience of performing everyday tasks, the negative implications connected to their usage largely remain unexplored. This study aims to explore the severity of privacy concerns and breaches related to the use of smart speakers. The research also extends to perceptions of general public and their attitudes towards the use of virtual assistant devices. Furthermore, it draws on the understanding of the European Union’s General Data Protection Regulation (GDPR) to draw the legal implications of data collection by corporations through these devices. Data for the study was retrieved through a thorough content analysis exercise from comments left by the general public under the Guardian UK’s media articles. Results from the primary research were organized into four themes; perception of devices, big brother is watching you, it’s a mad mad world and the convenience trade-off. The results were structured to explain of the various perceptions of general public towards these devices, from corporate to government surveillance. Lastly the results explore the ease and convenience and ease of using these devices against their inherent privacy risks. The findings and analysis of the study reflected the data interpreted by the researcher and the existing literature reviewed for this research. Lastly, the study concludes that although there are various layers to these privacy concerns from state surveillance to the tipping point of AI, the utility provided by these devices has the ability to mitigate those concerns. However the study also reveals that it is now incumbent on corporations to strengthen the security of these devices so the move towards a technologically advanced world is free of intrusive surveillance.